Crystallizable Fragment Glycoengineering for Therapeutic Antibodies Development - Li, Wei; Zhu, Zhongyu; Chen, Weizao; Feng, Yang; Dimitrov, Dimiter S. (Frontiers in Immunology, 2017)
Monoclonal antibody (mAb) based therapeutics are the fastest growing class of human pharmaceuticals. They are typically IgG1 molecules with N-glycans attached to the N297 residue on Fc. Different Fc glycoforms impact their effector function, pharmacokinetics (PK), stability, aggregation, safety and immunogenicity. Fc glycoforms affect mAbs effector functions including ADCC and CDC by modulating the Fc-FcγRs and Fc-C1q interactions. While the terminal galactose enhances CDC activity, the fucose significantly decrease ADCC. Defucosylated IgGs are thus highly pursued as next-generation therapeutic mAbs with potent ADCC at reduced doses. A plethora of cell glycoengineering and chemoenzymatic glycoengineering strategies are emerging to produce IgGs with homogenous glycoforms especially without core fucose. The chemoenzymatic glycosylation remodeling also offers useful avenues for site-specific conjugations of small molecule drugs onto mAbs. Herein, we review the current progress of IgG Fc glycoengineering. We begin with the discussion of the structures of IgG N-glycans and biosynthesis followed by reviewing the impact of IgG glycoforms on antibody effector functions and the current Fc glycoengineering strategies with emphasis on Fc defucosylation. Furthermore, we briefly discuss two novel therapeutic mAbs formats: aglycosylated mAbs and Fc glycan specific antibody drug conjugates (ADCs). The advances in the understanding of Fc glycobiology and development of novel glycoengineering technologies have facilitated the generation of therapeutic mAbs with homogenous glycoforms and improved therapeutic efficacy.